Hybrid cloud for dummies (Wiley, 2012)
Hybrid clouds are transforming the way that organizations do business. This handy guide helps you find out what this new cloud deployment model is all about. You'll get down- to-earth information about cloud technology, questions to consider, and how to plan and deliver your move to a hybrid environment